A Jewish kapo in Auschwitz : history, memory, and the politics of survival - Friling, Ṭuvyah 1953- (The Schusterman series in Israel studies, 2014)
This book presents the biography of Eliezer Gruenbaum (1908{u2013}1948) who was a Polish Jew denounced for serving as a Kapo while interned at Auschwitz. He was the communist son of Itzhak Gruenbaum, the most prominent secular leader of interwar Polish Jewry who later became the chairman of the Jewish Agencyu2019s Rescue Committee during the Holocaust and Israelu2019s first minister of the interior.--Publisher's description